RETRACTED: Increasing the role of transport enterprises in strengthening the financial stability of the region - Khasanov Bakhodir; Hasanova Risolat; Akramov Golibjon; Nurmanov Karjaubay; Akramov Abdulla (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001